Generalized difference sequence spaces on seminormed space defined by Orlicz functions - Tripathy, Binod Chandra; Altin, Yavuz; Et, Mikail (Versita, 2008)
In this paper we define the sequence space l(M) (Delta(m), p, q, s) on a seminormed complex linear space by using an Orlicz function. We study its different algebraic and topological properties like solidness, symmetricity, monotonicity, convergence free etc. We prove some inclusion relations involving l(M) (Delta(m), p, q, s).
Keywords: Orlicz function; difference sequence; solid space; symmetric space; sequence algebra